Deconstructing Eurocentric Narratives: A Critical Analysis of Civilization through the Works of Guizot, Gobineau, and Buckle - Shahzada Rahim Abbas (Journal of Islamic Thought and Civilization, 2026)
This article critically analyzes the Eurocentric conception of civilization through the canonical writings of three major Western historians; François Guizot, Arthur de Gobineau, and Henry Thomas Buckle, proposing a deconstructive analysis through the lens of broader historical and cultural perspectives. By employing the critical textual analysis informed by the deconstructive approaches, the study explores the development of Eurocentric frameworks of civilization to reveal how the underlying cultural, racial and teleological assumptions played a key role in shaping the understanding of three influential European historians. Starting with Guizot’s focus on teleological framework, Gobineau’s racial determinism, and Buckle’s enviromental determinism, the paper critically deconstructs the generalizations and inherent precincts of their civilizational frameworks. The paper challenges the idea that European civilization stands as the exclusive model of human progress, highlighting how these theorists overlook the intricate interactions of social, cultural, and economic forces that contribute to the development of civilizations. Through a detailed comparative and textual analysis, the article discursively explores how the teleological model of Guizot, the racial hierarchic model of Gobineau, and the environmental determinism framework of Buckle conceptualizes the term civilization as a sole achievement of the European endeavors while neglecting the contributions of the non-European societies, thus legitimizing the world order based on hierarchies. With these findings, the study contributes to historical literature by exposing the ideological basis of Eurocentric historiography of the 19th century.